2022
DOI: 10.1002/nur.22284
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture for depression: A systematic review and meta‐analysis

Abstract: Acupuncture is widely accepted as a therapeutic option for managing depression. However, evidence from clinical trials remains controversial. This review aims to synthesize the best available evidence on the efficacy and safety of acupuncture in managing depression. The review was performed according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analysis) guidelines. Five databases and the relevant trial registries were searched from the inception to October 2021. Randomized clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
1
0
Order By: Relevance
“…In previous reviews ( Wang et al, 2008 ; Zhang et al, 2010 , 2023 ; Armour et al, 2019 ; Chen et al, 2022 ), it was acknowledged that acupuncture, either alone or as an adjunct to pharmacological treatment, offers clinical benefits and can be considered as a safe therapeutic option for depression. However, many past reviews have had significant limitations concerning disease classification, inclusion criteria, and basis assessment.…”
Section: Discussionmentioning
confidence: 99%
“…In previous reviews ( Wang et al, 2008 ; Zhang et al, 2010 , 2023 ; Armour et al, 2019 ; Chen et al, 2022 ), it was acknowledged that acupuncture, either alone or as an adjunct to pharmacological treatment, offers clinical benefits and can be considered as a safe therapeutic option for depression. However, many past reviews have had significant limitations concerning disease classification, inclusion criteria, and basis assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, after the combination therapy the signi cant differences in urinary speci c metabolites including malonic acid (fatty acid biosynthesis), glutathione (glutamate metabolism), cysteine (glutamate metabolism), tryptophan (tryptophan metabolism were observed [18]. A systematic review and meta-analysis concluded that acupuncture, either in isolation or as a complementary therapy and along with pharmacological therapy, can be safe and effective for depression management [30]. A meta-regression of randomized controlled trials showed a direct association between the number of acupuncture sessions and symptom improvement in depressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to manual acupuncture, EA offers improved control over stimulation parameters, as well as greater repeatability and objectivity ( 13 ). There is emerging evidence indicating the therapeutic potential of EA in addressing psychological disorders such as anxiety and depression ( 14 17 ). EA has also been used in PPD treatment, showing specific therapeutic benefits.…”
Section: Introductionmentioning
confidence: 99%